Spatial-temporal characteristics of the oceanic bottom mixed layer in the South China Sea - Liu, Wenhu; Wang, Guihua; Chen, Changlin; Zhou, Muping (Frontiers in Marine Science, 2023)
The oceanic bottom mixed layer (BML) plays an important role in transporting mass, heat, and momentum between the ocean interior and the bottom boundary. However, the spatial-temporal variability of the BML in the South China Sea (SCS) is not well understood. Using 514 full-depth vertical profiles of temperature and salinity collected during the time period from 2004 to 2018 and time series of longer than one year from two particularly deployed hydrographic moorings, temporal and spatial variations of the BML have been analyzed. It has been found that the BML in the SCS has significant inhomogeneity. In particular, while the BML is relatively thin and stable over the continental shelf and in deep-sea regions, it is thick and unstable over the northern continental slope. The mean, median, and one standard deviation values of BML thickness over the entire SCS are 73 m, 56 m, and 55 m, respectively. Further analysis reveals that energetic high-frequency dynamic processes, together with steep bottom topography (large slope and roughness), cause strong tidal dissipation and vertical mixing near the bottom over the continental slope, resulting in thicker BMLs there. In contrast, the dynamic processes in the deep ocean are less energetic and low-frequency and the topography is relatively smooth (smaller slope and roughness), the tidal dissipation and bottom vertical mixing are weaker, therefore the BML is relatively thin. These findings enhance our understanding of the BML dynamics in the SCS and other marginal seas and provide insights to improve parameterizations of physical processes in ocean models.